Overview of the Dissertation Process within the Framework of Flow Theory: A Qualitative Study - Cakmak, Esra; Isci, Sabiha; Uslu, Fatma; Oztekin, Ozge; Danisman, Sahin; Karadag, Engin (EDAM, 2015)
The purpose of this study is to examine the flow of doctoral students who are also research assistants and in the dissertation process. The study was designed using the case study method. The case undertaken in the study was the dissertation process. Eleven participants were selected into the study using maximum variation sampling. Face-to-face, semi-structured interviews were conducted with the participants. Descriptive analysis was used to analyze the transcripts. The descriptive analysis of the data identified four main themes: (i) personal characteristics, including tackling challenges, sense of responsibility and planned work habits; (ii) interest in the field, including decision making about postgraduate education, satisfaction from postgraduate education, the fit between the doctoral field and the student's interests and skills, and academic goals; (iii) emotional attachment, including enjoyed stages of the dissertation process, feelings aroused by the dissertation, and concentration on the dissertation process; and (iv) living the flow.
Keywords: Flow theory; Dissertation process; Attachment to the job; Case study; STUDENTS; WORK; EXPERIENCE; ENVIRONMENTS; LEISURE; Education & Educational Research